Teacher (de)motivation from an Activity Theory perspective: Cases of two experienced EFL teachers in South Korea. (April 2016) - Song, Bongsun; Kim, Tae-Young
Abstract: In this study, we explore the teaching motivation of two experienced South Korean teachers of English from an Activity Theory perspective. In the fall semester of 2013, we interviewed two female teachers with a similar amount of teaching experience in comparable school districts as study participants in an in-depth qualitative inquiry. Our findings indicated that teachers' beliefs about effective teaching methods functioned as a crucial mediational tool for their teaching motivation, and that the two teachers' motivation levels progressed differently depending on how each of them exercised agency as a teacher. This study implies that, like L2 learning motivation, L2 teacher motivation also changes over time via dynamic interactions between the agents and contextual factors in an activity system. Pedagogically, the implication is that school administrators should be required to help teachers adjust to students' differing needs by providing a supportive learning environment.